Functionalized DVB-based polymer catalysts for glycerol and CO2 catalytic conversion. (December 2018) - Song, Xianghai; Wu, Yuanfeng; Pan, Donghui; Zhang, Jiahui; Xu, Siquan; Gao, Lijing; Wei, Ruiping; Xiao, Guomin
Graphical abstract: Preparation of glycerol carbonate from glycerol and CO2 over polymer catalysts functionalized with ionic liquid groups. Highlights: Several polymer catalysts were prepared and applied for the preparation of glycerol carbonate. The polymer functionalized with ionic liquid groups presented the best catalytic performance. Glycerol served as both reactant and co-catalyst during the reaction. The catalyst was highly recyclable. Abstract: In the present work, several DVB-based polymer catalysts were prepared and used for the synthesis of glycerol carbonate (GC) from glycerol carbonylation with carbon dioxide (CO2 ). Propylene oxide (PO) was introduced as a coupling reagent into the reaction to disturb the thermodynamics limitation. The characterization results confirmed the successful preparation of the functionalized polymer catalysts. P-DVB-(vIm-BuBr) showed the best catalytic performance among the prepared polymers. The high catalytic activity of P-DVB-(vIm-BuBr) was attributed to the presence of ionic liquid groups in the structure of the polymer. In addition, the preparation method had a significant influence on the catalytic activity of the polymer. Functionalization of the monomer with n-butyl bromide before polymerization could increase the content of ionic liquid groups of the polymer catalysts. During the reaction process, glycerol served not only as a reactant, but also as a co-catalyst to facilitate the coupling of PO with CO2 . P-DVB-(vIm-BuBr) achieved PO conversions as high as 96% and GC yields of 81% under optimal reaction conditions. The catalyst was highly recyclable and maintained its catalytic activity after five reaction cycles.